Understory contrasts across experimental tropical forest restoration - Luis C. Beltrán; Marinés de la Peña-Domene; Henry F. Howe; Camila A. Marín-Marín; Flavio Márquez-Torres; Edith Rivas-Alonso; Lilia L. Roa-Fuentes; Neptali Sánchez; Cristina Martínez-Garza (Forest Ecology and Management, 2026)

Striatal dopamine synthesis capacity and its association with negative symptoms upon resolution of positive symptoms in first-episode schizophrenia and delusional disorder - Stephanie M. Y. Wong; Y. N. Suen; Charlotte W. C. Wong; Sherry K. W. Chan; Christy L. M. Hui; W. C. Chang; Edwin H. M. Lee; Calvin P. W. Cheng; Garrett C. L. Ho; Gladys Goh Lo; Eric Y. L. Leung; Paul K. M. Au Yeung; et al. (Psychopharmacology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Rodent suppression of seedling establishment in tropical pasture - Crystal A. Guzmán; Henry F. Howe; David H. Wise; Rosamond I. Coates; Jenny Zambrano (Oecologia, 2021)

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

Restored connectivity facilitates recruitment by an endemic large‐seeded tree in a fragmented tropical landscape - Marinés de la Peña‐Domene; Emily S. Minor; Henry F. Howe (Ecology, 2016)
Many large‐seeded Neotropical trees depend on a limited guild of animals for seed dispersal. Fragmented landscapes reduce animal abundance and movement, limiting seed dispersal between distant forest remnants. In 2006, experimental plantings were established in pasture to determine whether plantings enhance seed dispersal and, ultimately, seedling recruitment. We examined patterns of naturally recruited seedlings of Ocotea uxpanapana, a large‐seeded bird‐dispersed tree endemic to southern Mexico that occurs in the surrounding landscape. We used GIS and least‐cost path analysis to ask: (1) Do restoration efforts alter recruitment patterns? (2) What is the importance of canopy cover and likely dispersal pathways to establishment? Patterns of seedling establishment indicated that dispersal agents crossed open pastures to wooded plots. Recruitment was greatest under woody canopies. Also, by reducing movement cost or risk for seed dispersers, wooded canopies increased influx of large, animal‐dispersed seeds, thereby restoring a degree of functional connectivity to the landscape. Together, canopy openness and path distance from potential parent trees in the surrounding landscape explained 73% of the variance in O. uxpanapana seedling distribution. Preliminary results suggest that strategic fenced plantings in pastures increase dispersal and establishment of large‐seeded trees, thereby accelerating forest succession in restorations and contributing to greater connectivity among forest fragments.

Response of two prairie forbs to repeated vole herbivory - Amy T. Sullivan; Henry F. Howe (Oecologia, 2011)

Response of two prairie forbs to repeated vole herbivory - Amy T. Sullivan; Henry F. Howe (Oecologia, 2010)

Early seed fall and seedling emergence: precursors to tropical restoration - Henry F. Howe; Yuliana Urincho-Pantaleon; Marinés de la Peña-Domene; Cristina Martínez-Garza (Oecologia, 2010)

Seasonal sex allocation by Common Grackles? Comment - Henry F. Howe (Ecology, 2010)

Can forest fragmentation disrupt a conditional mutualism? A case from central Amazon - Maria Luisa S. P. Jorge; Henry F. Howe (Oecologia, 2009)

The anomalous Kentucky coffeetree: megafaunal fruit sinking to extinction? - David N. Zaya; Henry F. Howe (Oecologia, 2009)

Recruitment of Hornbill‐Dispersed Trees in Hunted and Logged Forests of the Indian Eastern Himalaya - PIA SETHI; HENRY F. HOWE (Conservation Biology, 2009)
Hunting of hornbills by tribal communities is widespread in logged foothill forests of the Indian Eastern Himalaya. We investigated whether the decline of hornbills has affected the dispersal and recruitment of 3 large‐seeded tree species. We hypothesized that 2 low‐fecundity tree species , Chisocheton paniculatus and Dysoxylum binectariferum (Meliaceae) bearing arillate fruits, are more dispersal limited than a prolifically fruiting drupaceous tree Polyalthia simiarum (Annonaceae), which has potential dispersers other than hornbills. We estimated the abundance of large avian frugivores during the fruiting season along transects in 2 protected and 2 disturbed forests. We compared recruitment of the tree species near ( Buceros bicornis ), Wreathed ( Aceros undulatus ), and Oriental Pied Hornbills ( Anthracoceros albirostris ) were significantly lower in disturbed forests, but sites did not differ in abundances of the Mountain Imperial Pigeon ( Ducula badia ). Overall, tree species showed more severely depressed recruitment of seedlings (77% fewer) and juveniles (69% fewer) in disturbed than in protected forests. In disturbed forests, 93% fewer seedlings of C. paniculatus were beyond parental crowns, and a high number of all seedlings (42%) accumulated directly under reproductive adults. In contrast , D. binectariferum and P. simiarum were recruitment rather than dispersal limited, with fewer dispersed seedlings surviving in disturbed than in protected forests. Results are consistent with the idea that disturbance disrupts mutualisms between hornbills and some large‐seeded food plants, with the caveat that role redundancy within even small and specialized disperser assemblages renders other tree species less vulnerable to loss of regular dispersal agents.

Prairie forb response to timing of vole herbivory - Amy T. Sullivan; Henry F. Howe (Ecology, 2009)
The timing of herbivory can be an important factor in the strength and direction of plant response to herbivore damage. To determine the effect of vole herbivory timing within a growing season on tallgrass prairie forbs, we used individual plant enclosures to limit vole access to three species, Desmanthus illinoensis , Echinacea purpurea , and Heliopsis helianthoides , in an experimental restoration in northern Illinois, USA. As part of a long‐term experiment, we implemented five vole access treatments in 2003: (1) vole access for the entire growing season, (2) early‐season access, (3) mid‐season access, (4) late‐season access, and (5) no vole access. We protected all plants from herbivory in the following growing season (2004) to test whether the effects of herbivory in one growing season carried over to the next. We also tested how restoration planting design, including seeding time (June or December) and density (35 or 350 seeds/m 2 of each species) affected patterns of herbivory and plant recovery. Vole access for the entire growing season was most detrimental for the growth and reproduction of all three species. In contrast, vole access for a portion of the growing season had different effects on the three species: Desmanthus growth and reproduction was negatively affected by early‐season access, Echinacea reproductive output was reduced by late‐season access, and Heliopsis was not affected by early‐, mid‐, or late‐season vole access. Negative effects of continual vole access carried over to the following growing season for Desmanthus and Heliopsis , but not for Echinacea . Effects of herbivory did not carry over to the next season for Echinacea and Heliopsis when plants were accessible to voles for only part of the growing season. In contrast, Desmanthus plants exposed to early‐season herbivory in one year continued to produce fewer seeds per plant after being protected from vole herbivory for a growing season. Planting density and planting season had mixed effects. Echinacea and Desmanthus were larger in plots planted in June, showing that restoration design continued to affect plant population dynamics seven years after seeding. However, there was no interaction between plant response to vole herbivory and restoration design.

Disperser limitation and recruitment of an endemic African tree in a fragmented landscape - Norbert J. Cordeiro; Henry J. Ndangalasi; Jay P. McEntee; Henry F. Howe (Ecology, 2009)
Forest fragmentation may have positive or negative effects on tropical tree populations. Our earlier study of an endemic African tree, Leptonychia usambarensis (Sterculiaceae), in the East Usambara Mountains of Tanzania, found poorer recruitment of seedlings and juveniles in small fragments compared to continuous forest, and concomitant reduction of seed‐dispersal agents and seed dispersal. However, the possibility that other biotic or abiotic consequences of the fragmentation process contribute to diminished recruitment in fragments was left open. Here we test whether excessive seed predation, diminished fecundity, low seed quality, or adverse abiotic effects acted independently or in concert with reduced seed dispersal to limit seedling and juvenile recruitment in fragments. Extended observations of disperser activity, a seed placement experiment, seed predator censuses, and reciprocal seedling transplants from forest and fragment sources failed to support the alternative hypotheses for poorer seedling and juvenile recruitment in fragments, leaving reduced seed dispersal as the most plausible mechanism. Poorer recruitment of this species in forest fragments, where high edge‐to‐area ratios admit more light than in continuous forest, is particularly striking because the tree is an early successional species that might be expected to thrive in disturbed microhabitats.

Reversal of fortune: plant suppression and recovery after vole herbivory - Henry F. Howe (Oecologia, 2008)

The Paradox of Forest Fragmentation Genetics - ANDREA T. KRAMER; JENNIFER L. ISON; MARY V. ASHLEY; HENRY F. HOWE (Conservation Biology, 2008)
Theory predicts widespread loss of genetic diversity from drift and inbreeding in trees subjected to habitat fragmentation, yet empirical support of this theory is scarce. We argue that population genetics theory may be misapplied in light of ecological realities that, when recognized, require scrutiny of underlying evolutionary assumptions. One ecological reality is that fragment boundaries often do not represent boundaries for mating populations of trees that benefit from long‐distance pollination, sometimes abetted by long‐distance seed dispersal. Where fragments do not delineate populations, genetic theory of small populations does not apply. Even in spatially isolated populations, where genetic theory may eventually apply, evolutionary arguments assume that samples from fragmented populations represent trees that have had sufficient time to experience drift, inbreeding, and ultimately inbreeding depression, an unwarranted assumption where stands in fragments are living relicts of largely unrelated predisturbance populations. Genetic degradation may not be as important as ecological degradation for many decades following habitat fragmentation.

Planting densities and bird and rodent absence affect size distributions of four dicots in synthetic tallgrass communities - Cristina Martínez-Garza; Sonali Saha; Veronica Torres; Joel S. Brown; Henry F. Howe (Oecologia, 2004)

Inherent Rarity in Community Restoration - Godfrey G. Maina; Henry F. Howe (Conservation Biology, 2000)
We explore the implications of an often overlooked fact in community restoration: most species, in real or synthetic communities, are infrequent or rare, a phenomenon we call “inherent rarity.” Whether from long‐term interactions of many factors affecting birth, death, and establishment within natural communities, or from short‐term interactions of recently created communities, species abundance distributions are roughly lognormal or even more attenuated. The greater the predisturbance species diversity of remnants or the planting diversity of restorations, and the smaller the area of a habitat patch, the more likely a large proportion of species will exist in populations so small that they are acutely or chronically vulnerable to local extinction. We suggest that habitat fragmentation will inevitably favor plants and animals that are highly mobile, early successional species, including many exotic weeds among plants, or species that are historically organized as metapopulations that happen to be common enough to function as such. We further explore rationales for countering the effects of inherent rarity, including connectivity from buffers, corridors, and stepping stones, and dominance suppression from seasonally appropriate mowing, grazing, or fire.

Spatial patterns of mortality in a Colorado desert plant community - Maria N. Miriti; Henry F. Howe; S. Joseph Wright (Plant Ecology, 1998)